2018
DOI: 10.1515/bmt-2017-0154
|View full text |Cite
|
Sign up to set email alerts
|

Long-term recording performance and biocompatibility of chronically implanted cylindrically-shaped, polymer-based neural interfaces

Abstract: Stereo-electroencephalography depth electrodes, regularly implanted into drug-resistant patients with focal epilepsy to localize the epileptic focus, have a low channel count (6-12 macro- or microelectrodes), limited spatial resolution (0.5-1 cm) and large contact area of the recording sites (~mm2). Thus, they are not suited for high-density local field potential and multiunit recordings. In this paper, we evaluated the long-term electrophysiological recording performance and histocompatibility of a neural int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 43 publications
2
22
2
Order By: Relevance
“…F4,F5) GFAP stains comparing resulting gliosis between two different geometries, including F4) floating and F5) Michigan MEAs are also provided. F1–F3) Adapted with permission under the Creative Commons Attribution BY‐NC‐ND 4.0 license . Copyright 2018, the Authors.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
See 1 more Smart Citation
“…F4,F5) GFAP stains comparing resulting gliosis between two different geometries, including F4) floating and F5) Michigan MEAs are also provided. F1–F3) Adapted with permission under the Creative Commons Attribution BY‐NC‐ND 4.0 license . Copyright 2018, the Authors.…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…They found that small electrodes (15 µm Michigan electrodes and microwire electrodes) reduce glial scarring markers, while cylindrically shaped wire shanks help to mitigate long term FBR by limiting BBB breach. Another study demonstrated that cylindrically shaped neural probes are feasible for maintaining single unit and multiunit activity long‐term and were also shown to elicit a less severe FBR compared to other MEA geometries (Figure ,F1–F3), such as those utilized in focal epilepsy treatment. Floating, untethered MEAs (Figure A) have also shown promise in reducing FBR severity (Figure ,F4,F5) .…”
Section: Microelectrode Array Modifications For Improving the Neural mentioning
confidence: 99%
“…In addition, spike sorting was performed on the recordings to extract the following single unit properties for comparison: single unit yield, amplitude of single unit spikes and isolation distance (see “ Spike sorting and calculation of single unit properties ” in the Methods section for more details). The latter is a measure commonly used to determine the quality of single unit clusters 59 , while the former are usual features used to assess the recording performance extracted under different conditions 27 , 61 . The unit yield as well as properties corresponding to the quality of single units (spike amplitude, isolation distance) are important measures that can demonstrate the practical usability of probes in electrophysiological experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, spike sorting was performed on the recordings to extract various single unit properties for comparison, such as the single unit yield, the amplitude of single unit spikes and the isolation distance (see section 2.7 for more details). The latter is a measure commonly used to determine the quality of single unit clusters [59], while the former are usual features used to assess the recording performance extracted under different conditions [27,61]. Example recordings and single unit spike (table 3), the difference between site positions was most remarkable in the range corresponding to the largest spikes (from −300 μV to −1000 μV; figure 10(a)).…”
Section: Resultsmentioning
confidence: 99%